773 Indian experience with patient safety in public health. (1st September 2016) - Srivastava, RK; Kumar, Anil
Abstract : Background: Safety of patients in tertiary care hospitals in India was found to be a big problem. 62.9% of unsafe injections are administered every year 1 in India. Estimated risk of HCAI is up to 20 times higher than industrialised countries and is approx 10% and 15–30% in acute care. 77% of all reported cases of counterfeit and substandard drugs are from developing countries. Methods: A longitudinal study on patient safety practice in 12 (6 public+6 private) multi-specialty hospitals* was conducted by DGHS from 2005–2011 with objective of identifying, analysing and improving the gaps in hospital patient safety system, so that it is compliant to WHO guidelines on patient safety 2005.The study took up safety practice for hand hygiene, surgery, injection, medication, blood transfusion, infection control and hospital waste management as core areas of hospital patient safety system. Data were collected & analysed annually and at the end of study. It provided for annual gap identification and introduction of corrective measure in each core area and also for system development at end of study in areas of advocacy, infrastructure, capacity building and funding for practice of patient safety in hospitals. Results: This study created a patient safety unit in DGHS, a patient safety committee in the hospitals, a targeted advocacy programme, guidelines for survey and root cause analysis, protocols for safety practice in hospitals, training manuals, standard reporting format for adverse events, supportive monitoring system, and annual and study- end evaluation of outcome in terms of mortality and adverse events . Policy and practice changes like introduction of auto-disable syringe in public health (2009), revision of guidelines for disposal and syringe/needle under bio-medical disposal rules (2010), introduction of antibiotic policy in tertiary hospitals, strengthening of pharmaco-vigilance programme took place during this period. Success stories, reports of hospital, study report and technical report were documented. Conclusions: The study was able to showcase relevance of patient safety system in tertiary hospitals for better quality outcome. *Safdarjang Hospital, Ram Manohar Lal Hospital, AIIMS, Kalawati Saran Hospital, G. B. Pant Hospital, and GTB Hospital in public Health Sector – 6 National Accreditation Board for Hospital and Healthcare Providers approved private hospitals of Max group MoHFW – Ministry of Health & Family Welfare HCAI – Hospital Care Associated Infections (CLEN Program Evaluation Network (IPEN) for Department of Family Welfare, MoHFW)